THE EFFECTIVENESS OF USING TWO STAY TWO STRAY IN TEACHING READING OF NARRATIVE TEXT AT THE FIRST GRADE STUDENTS OF SMAN 1 SRONO IN THE 2020/2021 ACADEMIC YEAR - Moh. Jamaludin Iqbal (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2021)
The Effectiveness of Using Two Stay Two Stray In Teaching Reading Of Narrative Text At The First Grade Students Of SMAN 1 SRONO In The 2020/2021 Academic Year. Reading not only helps students understand the text but also to reach and expand their knowledge especially in English. Reading comprehension in learning English is a process of understanding written ideas through meaningful interpretation and interaction with language. In studying reading material, students must be able to understand the reading text during the reading process. Two Stay Two Stray is a cooperative learning model that provides opportunities for groups to share results and information with other groups. Two stay two stray is used with the aim of directing students to actively discuss, question and answer, seek answers, explain and listen to material explained by friends. The main objective of this research is to find out how effective the Two Stay Two Stray (TSTS) technique is used in the learning process of reading narrative text. In this study, researchers used an experimental method by grouping students into two groups, namely the experimental group and the control group. The research subjects were students of class X SMAN 1 Srono Banyuwangi. In collecting data, the researcher made observations, giving tests in the form of pre-test, post-test, and documentation. The results of this study indicate that the Two Stay Two Stray (TSTS) technique is quite effective in learning to read narrative text and can improve students' reading ability of narrative text. This is evidenced by the increase in the average score of students before the research was conducted by giving the pre-test, namely 76.76, then the average value after giving the material using the TSTS method and giving the post-test was 87.74. The researcher concluded that by using the Two Stay Two Stray (TSTS) technique the learning process to read narrative text was very effective and could improve students' reading skills.